Evaluation of Aerosol Drug Delivery Options during Adult Mechanical Ventilation in the COVID-19 Era - Piers J. Naughton; Mary Joyce; Marc Mac Giolla Eain; Andrew O'Sullivan; Ronan MacLoughlin (MDPI AG, 2021)
Drug delivery devices used for aerosol therapy during mechanical ventilation to ease the symptoms of respiratory diseases provide beneficial treatment but can also pose challenges. Reflecting the significant changes in global guidance around aerosol usage and lung-protective ventilation strategies, seen in response to the COVID-19 pandemic, for the first time, we describe the drug delivery performance of commonly used devices under these conditions. Here, vibrating mesh nebuliser (VMN), jet nebuliser (JN) and pressurised metered-dose inhaler (pMDI) performance was assessed during simulated adult mechanical ventilation. Both standard test breathing patterns and those representatives of low tidal volume (LTV) ventilation with concurrent active and passive humidification were investigated. Drug delivery using a VMN was significantly greater than that with a JN and pMDI for both standard and LTV ventilation. Humidification type did not affect the delivered dose across all device types for standard ventilation. Significant variability in the pMDI dosing was evident, depending on the timing of actuation and the adapter type used. pMDI actuation synchronised with inspiration resulted in a higher delivered drug dose. The type of adapter used for pMDI actuation influenced drug delivery, with the highest dose observed using the CombiHaler.